Pharmacoeconomic Analysis of Antidiabetic Therapy in Patients with Type 2 Diabetes Mellitus - Safaruddin; Salbia; Putri Indah Sari; Rahmasinar Amin (Jurnal Kesehatan Cendikia Jenius, 2026)
Type 2 diabetes mellitus is a chronic disease with a continuously increasing prevalence and requires long-term therapy, resulting in a substantial financial burden. Pharmacoeconomic evaluation is therefore needed to assess the efficiency of antidiabetic therapy at Daya Regional General Hospital, Makassar City. This study aimed to analyze treatment costs, examine the relationship between treatment costs and treatment duration, and identify the most efficient therapy based on the Average Cost-Effectiveness Ratio (ACER) among patients with type 2 diabetes mellitus. This study employed a quantitative descriptive-analytical method with a retrospective approach involving 69 patients with type 2 diabetes mellitus treated from January to February 2026. Data were analyzed using Cost of Illness (COI), Cost-Effectiveness Analysis (CEA), and Spearman’s correlation test. The results showed that the average treatment cost per patient was IDR 576,170.65. A significant positive correlation was found between treatment duration and treatment cost (r = 0.239; p = 0.048). Single-drug therapy had the lowest ACER value of IDR 1,117,506.50 and the highest proportion of controlled HbA1c levels at 38.9%. In conclusion, single-drug therapy using oral antidiabetic drugs was the most cost-effective treatment option for patients with type 2 diabetes mellitus at Daya Regional General Hospital, Makassar, as it provided the highest clinical effectiveness at an affordable cost. It is recommended that pharmacoeconomic evaluation be one of the considerations in selecting antidiabetic therapy to obtain optimal clinical results at a more efficient cost.